Social representations of adolescents on sexual relations and the use of condoms - Elys de Oliveira Bezerra; Maria Lúcia Duarte Pereira; Ana Clara Patriota Chaves; Priscila de Vasconcelos Monteiro
The objective of this investigation was to identify how adolescents structure the social representations of sexual intercourse and use of condoms. Exploratory and descriptive research was conducted with a convenience sample consisting of 234 students of a public secondary school in Fortaleza-CE, Brazil, between July 2009 and April 2010. Data were collected using a questionnaire with variables on socioeconomic status and sexual behaviour, and Free Association test with three terms: 'sex', 'unprotected sex' and 'sex with a condom'. Sexual intercourse was represented by love and affection among the women, while men associated sex to pleasure, desire and attraction toward the female body. The condom was considered important by both groups, but men represented condoms as being something bad that restricts pleasure. Health professionals are granted the opportunity to identify vulnerabilities of this population to DST/HIV/AIDS and work with these vulnerabilities in the most appropriate way.